Preparation of Poly(Aniline-co-p-Nitro Aniline) by Spin-Coating and Study of the Effect of Thickness on Energy Gap - HUSSEIN, Hussein Falaihj (Walailak Journal of Science and Technology (WJST), 2013)
Thin films of a copolymer of aniline with p-nitro aniline were prepared from a dimethyl sulfoxide solution (DMSO) by spin-coating. The solution of the polymer was spread on cover glass and at room temperature. The optical properties of the poly(aniline-co-p-nitro aniline) were investigated at room temperature. An absorbance, transmission and reflectance were determined from UV-visible measurements. The absorption coefficients and bang gap of films material were developed. The thickness of the poly(aniline-co-p-nitro aniline) thin layer on the glass was determined at the range from 1055 to 2033 nm. doi:10.14456/WJST.2014.19